Dating violence prevention program - Vizcarra, María Beatriz; Poo, Ana María; Donoso, Trinidad (Revista de Psicología, 2013)
Approach strategies regarding dating violence are analyzed, with emphasis on primary and secondary programs with assessed results. Based on national and international findings and their own research, the authors developed an educational program "Building a healthy relationship with your partner" for university students in Spanish speaking countries, the main objective being the development of life skills in order to facilitate healthy partner relationships which exclude violence. Theoretical and pedagogical arguments, the general structure of the program and some preliminary results are described.